PENGARUH KONEKSI POLITIK, MEKANISME TATA KELOLA, UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN SEKTOR PERBANKAN YANG TERCATAT DI BURSA EFEK PERIODE (2021-2023) - Dimas Rama Pramudia; Hairul Anam; Yanzil Azizil Yudaruddin; Wiwik Saraswati (KRISNA: Kumpulan Riset Akuntansi, 2025)
The aim of this research is to find out whether political connections, governance mechanisms, company size influence the performance of banking sector companies listed on the IDX for the 2021-2023 period. The population used in this research was 141, which was obtained from the BEI website itself. In this research, it is known that political connections do not have a significant effect on company performance. which means political connections have no signal on company performance. However, it is different from the governance mechanism and company size. Governance mechanisms and company size have a significant effect on company performance, which means that governance mechanisms and company size have a positive signal on the performance of banking sector companies.